Considerations on asemic writing: the case of Mirtha Dermisache (Palíndromo, 2021)
The text addresses the writing of Argentine artist Mirtha Dermisache, one of the main devotees of asemic writing. Her texts unfold into a series of different writing systems in which we come across traits that develop from the concepts of repetition, alternation, symmetry and rhythm in a form of writing without a precise semantic content. As they lack words, the reader can only look at them.
Keywords: Asemic writing; Writing to see; Artist writing